PENGARUH OWNERSHIP STRUCTURE, PEMBERIAN REMUNERASI DIREKSI TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020: SEBELUM DAN MASA PANDEMI COVID-19 - Sylvia Safitri; Taufiq Hidayat (Ibs Press, 2023)
The purpose of this research is to analyze and to provide evidence of the effect of Ownership Structure, Directors’ Remuneration on Financial Performance. This study uses data from 40 banking companies listed on the Indonesia Stock Exchange in the period of 2016-2020. This research method uses secondary data with a sampling method in the form of purposive sampling. The hypotheses in this study were tested with descriptive statistics and multiple regression methods. The results of this study indicate that Managerial Ownership have no effect on financial performance before the COVID-19 and have a negative significant effect during the COVID-19. Directors’ Remuneration have a positive and significant effect on financial performance before and during the COVID-19 pandemic. The result of Institutional Ownership have a negative and significant effect on financial performance before the COVID-19, while during the COVID-19 pandemic Institutional Ownership have no effect on financial performance.